Betaine and nano-emulsified vegetable oil supplementation for improving carcass and meat quality characteristics of broiler chickens under heat stress conditions - Suliman, Gamaleldin M.; Hussein, Elsayed O. S.; Al-Owaimer, Abdullah N.; Alhotan, Rashed A.; Al-Garadi, Maged A.; Mahdi, Jameel M. H.; Ba-Awadh, Hani A.; Qaid, Mohammed M.; Swelum, Ayman Abdel-Aziz (Frontiers in Veterinary Science, 2023)
The aim of this research was to examine the effects of water-added betaine (BET) and/or nano-emulsified vegetable oil (MAGO) on carcass and meat quality characteristics of broilers raised under thermoneutral (TN) and heat stress (HS) conditions. On day 21, 640 birds (Ross 308) were randomly assigned to one of two thermal conditions (thermoneutral 22±1℃ and heat stress 32±1℃) each containing four treatment groups: Control, BET, MAGO, and a mixture of both (BETMAGO) in a 2x4 factorial arrangement. Each group has eight replicates, with ten birds each. The birds’ carcass and meat quality characteristics were evaluated at 35 days. The dressing percentage, breast, leg, wing, heart, initial pH, color change, cooking loss (CL), water-holding capacity (WHC), shear force (SF), and texture profile with exception of springiness significantly affected by the treatments. The results showed that HS had negative effects on carcass weight and relative weights of the breast, spleen and heart. Moreover, HS increased dressing percentage, wing, initial pH, final core temperature, initial lightness, WHC, and hardness. Significant differences of interactions between treatments*temperature were observed on the spleen, WHC, and SF. In conclusion, water supplemented with BET and/or MAGO effectively improved meat characteristics under HS conditions. More studies on the use of BET and/or MAGO at different levels were recommended.